Treatment-driven tumour heterogeneity and drug resistance: Lessons from solid tumours. (March 2022) - Crucitta, Stefania; Cucchiara, Federico; Mathijssen, Ron; Mateo, Joaquin; Jager, Agnes; Joosse, Arjen; Passaro, Antonio; Attili, Ilaria; Petrini, Iacopo; van Schaik, Ron; Danesi, Romano; Del Re, Marzia
Highlights: Tumour heterogeneity is one of the major causes of drug resistance. Therapy induces a selective pressure on resistant clones already present in tumour. Mechanisms of resistance allow new targeted therapies approaches. Abstract: Molecular heterogeneity characterizes tumours' evolution and adaptation and, because of its dynamics and continuous changes under external pressure, it is one of the major causes of drug resistance, contributing to therapy failure. Several studies reported evidence of molecular events occuring in individual tumours, including monoclonal or polyclonal resistance, and primary or secondary resistance mechanisms. While primary resistance is a phenomenon already present at the diagnosis of a tumor, the acquired one is strongly related to the selective pressure of treatments administered. Therefore, the pharmacological characteristics of a drug, including its potency, binding affinity and structure, largely influence the mechanism of resistance that will arise at the progression of the disease. As an example, the lung cancer experience clearly demonstrated that the highest is the potency of a drug on its target, the more are the possibilities that the mechanism of resistance will arise independently of the target itself. The present review is focused on tumour heterogeneity and its relation to resistance to targeted-therapy, based on treatment selective pressure across different tumour types, including lung, colorectal, prostate, breast cancer and melanoma. The mechanisms of resistance based on the drug potency and the selective pressure of treatments are discussed, leading to new drug developments or new therapeutic combinations.